Predictors of Students’ Academic Performance in Science 7 Using Alternative Delivery Mode - Cabugnason, Angel Rose; Linaugo, Joji (Technium Education and Humanities, 2023)
The COVID-19 pandemic brought an abrupt change in the world, including the educational system. To prevent academic freeze, and for the public safety, distance learning is adopted, and in Philippines, modular learning is adopted in general. Science is a subject that is considered difficult, and it challenged the teachers in making the students grasp the concepts well, most especially to the Grade 7 students who transition to secondary school. A descriptive correlational research design was used to determine the predictors of students’ academic performance in Science 7 using Alternative Delivery Mode (ADM)-modules at a secondary school in Central Philippines. These predictors which some are found in the Learner Enrollment and Survey Form (LESF) are age, sex, learning styles, academic achievement in English, utilization of gadget, parents’ educational attainment, and family income. Fifty-two (52) Grade 7 students were taken as respondents through stratified sampling technique. A 40-item multiple-choice validated researcher-made questionnaire that covers the Most Essential Learning Competencies (MELCs) from the first to second quarters was administered to the respondents. The results of the test in Science 7 are interpreted as Low/Below Standard. From the seven variables tested for the study, it is only the learning style that weakly predicts students’ academic performance in Science 7 using Alternative Delivery Mode (ADM) modules. It is recommended that teachers should provide set of activities catering different learning styles of the students that the modules/learning activity sheets will be enhanced to improve the students’ performance.